GEREJA DALAM PERSIMPANGAN: LEMBAGA SWADAYA MASYARAKAT ATAU LEMBAGA ADIKODRATI PENGEMBAN MANDAT ILLAHI - Imanuel Sukardi; Samuel Purdaryanto (Sesawi, 2021)
Church must be understood as supernatural spritual institution as bearers of divine mandates on this earth, spiritual mandates and social mandates, be spiritual blessing and physical blessing. Church has taken the form of formal and legal institutions as such as social institutions. Then,the problems are the character and the impact of churches are not better than the social institution. Its because they lost their boot mandates. Those mandates originate and move from two church shahadas,love God and love others. The ambivalance among shahada and character,mandate and function cause churches are on intersection of become social institution or a spiritual institution. To back to their origin function,churches face two challenges. They are bravery to take off the deadly tradition,system,and theologies and then back to biblical tradition,system,and theologies.